The Legacy of Early fraciscan Thought - Schumacher, Lydia (Veröffentlichungen des Grabmann-Institutes zur Erforschung der mittelalterlichen Theologie und Philosophie, 2021)
The influence of later medieval fraciscans on subsequent scholarly developments has been widely acknowledged. However, the legacy of early fraciscan thought, as it developed in fraciscan thinkers who worked in the first half of the 13th century, remains unknown. Leading scholars of both periods illustrate the role that the early fraciscan tradition played in forming the later fraciscan tradition and the traditions that it influenced in turn.